2023
DOI: 10.3390/ani13162602
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Indicators of Pain and Suffering in Arthropods and Might Pain Bite Back?

Abstract: Pain in response to tissue damage functions to change behaviour so that further damage is minimised whereas healing and survival are promoted. This paper focuses on the behavioural criteria that match the function to ask if pain is likely in the main taxa of arthropods. There is evidence consistent with the idea of pain in crustaceans, insects and, to a lesser extent, spiders. There is little evidence of pain in millipedes, centipedes, scorpions, and horseshoe crabs but there have been few investigations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 133 publications
0
12
0
Order By: Relevance
“…Still, this is an intriguing and relevant problem, and scientists have approached it with many different techniques, measuring physiological responses and behavioural actions. Pain is a particular problem for welfare as it is important to any animal and yet is perceived to include sensory, cognitive, and difficult-to-know affective aspects [36]. Sneddon et al [37] lay out a series of possible investigations that might evaluate pain in animals, including sensory abilities, connections to the brain, and areas within the brain that process such information.…”
Section: Can Science Partner With Philosophy To Promote Animal Welfare?mentioning
confidence: 99%
“…Still, this is an intriguing and relevant problem, and scientists have approached it with many different techniques, measuring physiological responses and behavioural actions. Pain is a particular problem for welfare as it is important to any animal and yet is perceived to include sensory, cognitive, and difficult-to-know affective aspects [36]. Sneddon et al [37] lay out a series of possible investigations that might evaluate pain in animals, including sensory abilities, connections to the brain, and areas within the brain that process such information.…”
Section: Can Science Partner With Philosophy To Promote Animal Welfare?mentioning
confidence: 99%
“…Various lists of criteria have been constructed, some long [2] and some short [6]. Because the function of pain seems to involve a relatively long-term alteration of behaviour, it has been suggested that an emphasis be put on behaviour that is not easily explained by reflexes [7]. The more that criteria are fulfilled for a particular taxon, the more likely it is that members of the taxon experience pain.…”
Section: Introductionmentioning
confidence: 99%
“…One behavioural criterion for pain is that it should elicit behaviour directed toward the site of the noxious stimulus, or protection of that site by guarding or limiting the use of that part of the body [2,6,7]. For example, we expect to see rubbing, licking, holding, guarding, or limping, which can be too complex and prolonged to be explained by reflexes, and these behaviours have been noted in a broad range of animals [2].…”
Section: Introductionmentioning
confidence: 99%
“…Sentience is generally considered a precondition for the consideration of welfare (though see Dawkins 2017 ) and there is currently no scientific consensus on insect sentience (Adamo 2016 , 2019 ; Barron & Klein 2016 ; Klein & Barron 2016 ; Gibbons & Sarlak 2020 ; Mikhalevich & Powell 2020 ; Lambert et al. 2021 ; Loon & Bovenkerk 2021 ; Overgaard 2021 ; Kakrada & Colombo 2022 ; Elwood 2023 ; Voulgari-Kokota et al 2023 ; Barrett & Fischer 2024 ).…”
Section: Introductionmentioning
confidence: 99%